Correlation Analysis of Soil Nutrients and Quality Index in Pepper Planting Areas - Chuanjing Liang; Dan Xing; Jianwen He; Dehui Tu; Yongping Wang (Agronomy)
This study explores the correlation between soil nutrient elements and pepper fruit quality in Guizhou Province, highlighting regional variations in nutrient influence. Guizhou, with its unique mountainous and karst terrain, provides a distinct ecological environment for pepper cultivation. Our analysis of three major pepper-growing regions—Dafang, Guiyang, and Zunyi—demonstrates that the nitrogen, phosphorus, and potassium levels in the soil significantly impact pepper quality. Potassium plays a particularly vital role in fruit development, as deficiencies in potassium often result in flower and fruit drop and reduced yield. In Dafang, AP (available phosphorus) and TK (total potassium) were most closely linked to amino acids, reducing sugars, and capsaicinoid content, while in Bozhou, SAN (available nitrogen) was most influential, and in Qingzhen, TP (total phosphorus) and AK (available potassium) were predominant. The findings suggest that key soil elements, such as available phosphorus, available potassium, available nitrogen, and organic matter, influence the quality indicators—amino acids, reducing sugars, capsaicin, and dihydrocapsaicin—in pepper fruits. Further analysis indicates that Guizhou’s distinct soil composition significantly contributes to its peppers’ unique flavor profile. The combined effects of soil nutrients, pepper varieties, and cultivation practices underline the superior quality of Guizhou peppers. This study provides a foundation for understanding the soil–quality interaction and enhances the market recognition of Guizhou’s pepper varieties. Future research should investigate the integrated effects of environmental and soil factors to better assess Guizhou’s favorable growth conditions for peppers.